Cellular and immunological biomarkers in Pacific oyster Crassostrea gigas (Thunberg, 1793) reared in a tropical estuary during rainy season - Loján Avellán, Mariela Carolina (2021)
Tropical estuaries have been considered excellent environments to develop the oyster culture Crassostrea gigas; however, there are limiting factors during the rainy season that modulate changes in physiological and cellular responses, which affect oyster survival. In this study, cellular and immunological biomarkers, growth and survival of C. gigas were evaluated in suspending culture in the estuary of the Chone River (Ecuador), from December 2019 to March 2020. Environmental parameters (pluviosity, salinity and temperature) and in vitro cellular-immunological biomarkers (viability, count of hemocytes, phagocytosis and lysosomal membrane stability) and catalase activity from coelomic fluid were determined. The monthly average of precipitation showed an increase since January (78,8 mm), with a maximum value in February (174,8 mm), decreasing progressively in March (53,2 mm). The temperature varied between 26 and 32° C, the salinity decreased from 32 ups in December to 10-14 ups in February and March respectively. The organisms evaluated during February and March showed a reduction (4-5%) in surrounding hemocyte viability, and more than 14% showed destabilization of the lysosomal membranes. Phagocyte number increased and catalase activity decreased during these months. Oysters showed a low daily growth rate (0,01 mm/day), and survival decreased to 64% (March). The cellular-immune system in reared oysters is modulated by low salinity and increased water surface temperature, suggesting a direct relationship with growth and survival. The cellular and immunological biomarkers evaluated are recommended as indices of physiological condition in C. gigas under culture. Keywords: catalase; growth; stress; phagocytosis; hemocytes; neutral red retention